Simple Integrated Agriculture at SDN Megale I Kedungadem with Teaching Campus Students - Zani, Rihma Zaw; Syah, Mirza Andrian (Jurnal Pengabdian Masyarakat Bestari, 2024)
Agriculture is an important aspect in obtaining food and staples for the processing industry. Integrated agriculture is a combination of agriculture and fisheries that form a unified system. The purpose of this research activity is to introduce school residents to simple integrated agriculture. The method used is a qualitative research method in the form of natural observation. The result obtained is that school residents are enthusiastic about learning about simple integrated agriculture. Simple integrated agriculture can be implemented by people who want to be independent in meeting food needs.